STUDENTS’ SPEAKING ABILITY THROUGH COMMUNITY LANGUAGE LEARNING - Abdullah, Mirawati (Elite : English and Literature Journal, 2017)
Abstract This research aimed at finding out how the community language learning improves speaking ability and how does the community language learning enhances the interest of students to speak English in speaking class. This research applied quasi-experimental method. The research data were collected through speaking test and questionnaire. The speaking test was given in the form of interview to know the students’ achievement on speaking ability and the questionnaire was to know the students’ interest toward community language learning in speaking class. The findings on speaking ability of the participants were analyzed by using independent sample t-test and the students’ interest was analyzed by using descriptive statistics. The study concluded that: (1) Community Language Learning improve the first semester students of SMP Negeri 19 Makassar to speak English significantly better than conventional method, and (2) the participants were highly interested in speaking English by community language learning. Abstrak Penelitian ini bertujuan: (1) untuk menemukan apakah penggunaan community language learning dapat mengembangkan kemampuan berbicara siswa daripada metode lama, (2) dan apakah penggunaan community language learning menigkatkan minat siswa. Metode penelitian ini menerapkan quasi experimental. Data penelitian dikumpulkan dengan mengunakan dua Instrumen; Tes speaking dan angket (skala likert). Tes speaking diberikan dalam bentuk wawancara untuk mengetahui prestasi siswa pada kemampuan berbicara bahasa Inggris dan angket unutk mengetahui minat siswa terhadap penggunaan community language learning. Hasil tes speaking dianalisa dengan menggunakan Independent sample t-test dan minat siswa dianalisa dengan menggunakan deskriptif statistic, hasil means score dari minat siswa 81.35. Kajian ini menyimpulkan bahwa (1) penggunaan community language learning mengembangkan kemampuan berbicara siswa secara significant lebih baik daripada metode biasa, (2) penggunaan community language learning meningkatkan minat siswa dalam berbicara menggunakan bahasa Inggris.